2004
DOI: 10.1002/gea.20011
|View full text |Cite
|
Sign up to set email alerts
|

Geoarchaeology and prehistory of the Kipsing and Tol river watersheds in the Mukogodo Hills region of Central Kenya

Abstract: An archaeological survey and geomorphological investigation were conducted over a period of three years in the Tol and Kipsing River valleys, both located in the Mukogodo Hills-Upper Ewaso Ng'iro Plains region of Central Kenya. Eleven alluvial-stratigraphic sections were studied, and five late-Quaternary alluvial stratigraphic units were identified on the basis of lithology, chronology, and soil stratigraphy. The locations of 63 archaeological sites recorded during the reconnaissance were compared with the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…There is also plentiful geomorphological evidence to suggest that rainfall regimes have fluctuated widely across the Ewaso Basin over the millennia. In commenting on the results of recent surveys in the Kipsing and Tol River watersheds in the Mukogodo Hills area immediately north of Lolldaiga, Pearl and Dickson (2004) noted that archaeological site distributions in these areas have been heavily affected by erosion and often reburied beneath recent alluvia. In all, Pearl and Dickson identified five stratigraphic units in this area, which related to different depositional events dated to between ca.…”
Section: Evidence For Human-induced Environmental Changementioning
confidence: 99%
“…There is also plentiful geomorphological evidence to suggest that rainfall regimes have fluctuated widely across the Ewaso Basin over the millennia. In commenting on the results of recent surveys in the Kipsing and Tol River watersheds in the Mukogodo Hills area immediately north of Lolldaiga, Pearl and Dickson (2004) noted that archaeological site distributions in these areas have been heavily affected by erosion and often reburied beneath recent alluvia. In all, Pearl and Dickson identified five stratigraphic units in this area, which related to different depositional events dated to between ca.…”
Section: Evidence For Human-induced Environmental Changementioning
confidence: 99%
“…More recently, the British Institute in Eastern Africa (BIEA) conducted research elsewhere on the plateau, primarily on Mugie and Lolldaiga Ranches (Lane 2005, forthcoming). Other studies at Laikipia have focused on Shulumai and Kakwa rockshelters in the Mukogodo Hills, near the southeastern part of the Plateau, where interest has centred on the emergence of anatomically modern humans and Middle Stone Age (MSA) and Later Stone Age (LSA) occupations (Gang 2001;Dickson and Gang 2002;Dickson et al 2004;Pearl and Dickson 2004). Siiriäinen (1977Siiriäinen ( , 1984 excavated three rock shelters located on Kisima Farm near the town of Rumuriti in the northern part of the Plateau: KFR-A4, A5, and A12.…”
Section: History Of Archaeological Research At Laikipiamentioning
confidence: 99%
“…Research in the Mukogodo Hills of Central Kenya has demonstrated that LSA inhabitants of the region engaged in a centrally organized resource procurement strategy emanating from rockshelter processing areas and open-air food procurement sites Mutundu, 1998: 218-228;Pearl and Dickson, 2004). The earliest PN components in the region date to ca.…”
Section: Archaeological Background To the Study Areamentioning
confidence: 99%
“…Archaeological sites bearing artifacts of modern Homo sapiens occur in nearly all ecosystems of East Africa. However, valley fill associated with large rivers that drain eastern Africa contain an impressive and instructive archaeological record for the Late Pleistocene and Holocene (e.g., Abungu, 1989;Chami and Kweksason, 2003;Dickson et al, 2004;Pearl and Dickson, 2004;Wright, 2005a). Sediment deposition and artifact preservation conditions associated with fluvial systems and a dearth of permanent water sources across large swaths of land provide archaeologically pristine case studies for studying the ways humans have managed resources over the last several thousand years.…”
Section: Introductionmentioning
confidence: 99%